Development of Android programs for scientific computation - Li, Wenshu (2018)
Micro-strip line has become a key component in determining the performance of high-speed digital, RF and microwave circuits [1]. Approximate model can be used to design the micro-strip traces. By understanding the micro-strip transmission line, designers can properly build these structures to meet their needs. However, complex calculations behind micro-strip line theory makes it difficult to understand and use. Although there are many micro-strip line calculators available on-line to help people learn and use conveniently, the micro-strip line circuit design application is rarely seen on pads or phones. This dissertation gives an insight into the development of android based application which can help students gain a better understanding of RF circuits. This application enables the users to calculate micro-strip line parameters and design its circuits. It will also show insertion losses, attenuation losses versus frequencies.